Removal efficiencies of constructed wetland planted with Phragmites and Vetiver in treating synthetic wastewater contaminated with high concentration of PAHs - Alsghayer, Rabia; Ali, Salmiaton; Mohammed, Thamer Ahmed; Idris, Azni; Ishak, Che Fauziah (MDPI, 2020)
This study aimed to evaluate the capability of horizontal subsurface flow constructed wetlands (HSFCWs) in treating contaminated wastewater with a high concentration of polycyclic aromatic hydrocarbons (PAHs) (Phenanthrene, Pyrene, and Benzo[a]Pyrene), using two plants, namely Phragmites and Vetiver. The investigated parameters were (1) PAHs uptake by the plants, (2) PAHs removal efficiencies, (3) accumulated PAHs in the soil of CWs, (4) shoot/root concentration factor, (5) translocation factor, and (6) PAHs correlation to lipid contains in the plants. During the treatment period, the results showed that the highest concentration of Phenanthrene in the shoot and the root systems of Phragmites, was 229.3 and 192 μg/g; Pyrene was 69.1 and 59.2 µg/g; and Benzo[a]Pyrene 25.1 and 20.2 µg/g, respectively. Meanwhile, in the Vetiver shoot and root systems were Phenanthrene 87.5 and 64.1 µg/g; Pyrene 63.2 and 42.1 µg/g; and Benzo[a]Pyrene 21.3 and 27.3 µg/g, respectively. The removal rates of Phenanthrene, Pyrene, and Benzo[a]Pyrene (PAHs compounds) by the CW planted with Phragmites were found to be 83%, 71%, and 81%, respectively, while the removal rates by CW planted with Vetiver were found to be 67%, 66%, and 73%, respectively. Moreover, the removal rates by unplanted CW were found to be 62%, 58%, and 55%, respectively. The results indicated that the HSFCW planted with Phragmites has an effective pathway to remove high concentrations of PAHs.